Pakistan : Staff Report for the 2000 Article IV Consultation and Request for Stand-By Arrangement. (IMF Staff Country Reports; Country Report, 2001)
Pakistan showed good macroeconomic performance over the past years. Executive Directors welcomed the program, which aimed at strengthening the balance-of-payments position, rebuilding official reserves, and reducing public sector indebtedness. They emphasized the need for revenue mobilization, improving investor confidence, poverty alleviation, good governance, tightening fiscal and monetary policies, and improvement in the collection, quality of data, and transparency. They approved financial support for the country's economic developments under the Stand-By Arrangement.